Evidence-based pediatric infectious diseases - Isaacs, David 1950-; Elliott, Elizabeth J.; Gilbert, Ruth; Moyer, Virginia; Pichichero, Michael (Malden, Mass. Oxford BMJ/Blackwell, 2007)
A practical guide to the diagnosis and management of childhood infections in clinical practice. The author and an expert consultant editor team critically looks at the evidence for decision making in pediatric infections. Clear summaries and specific guidance allow you to assess the evidence for yourself and make rapid but informed management decisions based on the strength of evidence available. Antibiotic doses are presented clearly and simply, enabling you to select appropriate treatment at a glance. This resource uses a case-based approach that focuses on the most common disease areas affecting children in industrialized countries, developing countries, travelers and refugees. It is an up-to-date, relevant and widely applicable text that carefully examines the evidence for antibiotics and other interventions whilst encouraging a conservative and responsible approach to antibiotic use.
Evidence-based practice -- Rational antibiotic use -- Cardiac infections -- Cervical infections -- Eye infections -- Fever -- Gastrointestinal infections -- HIV infection -- Immune deficiency -- Meningitis and central nervous system infections -- Osteomyelitis and septic arthritis -- Respiratory infections -- Sexually transmitted and genital infections -- Skin and soft tissue infections -- Systemic sepsis -- Tropical infections and travel -- Urinary tract infections -- Viral infections.
Includes bibliographical references and index.
Keywords: Children; Communicable diseases in children; Communicable diseases; Evidence-based medicine; Evidence-based pediatrics